Compared analysis of the school day in European Union countries - Parente, Cláudia Da Mota Darós [UNESP]; Nakano, Natália (FapUNIFESP (SciELO), 2020)
This article aims to analyze the school days in European Union countries, systematizing similarities and differences between education systems. The compared analysis involved fifteen member countries and focused on the descriptive and comparative phases of the classical comparative method. School days are socio-historical and cultural constructions, which result in sometimes convergent, sometimes divergent policies in the region. In general, the compulsory school day in European countries is from 5 to 6 hours per day. However, there are many features, including investment in policies that integrate curricular and extracurricular activities, as supervised socio-educational times. Through compared analysis, it was possible to identify perspectives and alternatives to the school day configuration to better answer to the demands and needs of the subjects of education.
Análisis comparado de la jornada escolar en países de la unión europea
Analyse comparée de la journée scolaire des pays de l’union européenne
Keywords: Education system; Educational policy; European union; School day